VICS82: The VISTA-CFHT Stripe 82 Near-infrared Survey - Geach, J. E. (2017)
We present the VISTA-CFHT Stripe 82 (VICS82) survey: a near-infrared (J+K s ) survey covering 150 square degrees of the Sloan Digital Sky Survey (SDSS) equatorial Stripe 82 to an average depth of J = 21.9 AB mag and K s = 21.4 AB mag (80% completeness limits; 5σ point-source depths are approximately 0.5 mag brighter). VICS82 contributes to the growing legacy of multiwavelength data in the Stripe 82 footprint. The addition of near-infrared photometry to the existing SDSS Stripe 82 coadd ugriz photometry reduces the scatter in stellar mass estimates to σ log(M ∗ ) ≈ 0.3 dex for galaxies with M ∗ > 10 9 M ⊙ at z ≈ 0.5, and offers improvement compared to optical-only estimates out to z ≈ 1, with stellar masses constrained within a factor of approximately 2.5. When combined with other multiwavelength imaging of the Stripe, including moderate-to-deep ultraviolet (GALEX), optical and mid-infrared (Spitzer-IRAC) coverage, as well as tens of thousands of spectroscopic redshifts, VICS82 gives access to approximately 0.5 Gpc 3 of comoving volume. Some of the main science drivers of VICS82 include (a) measuring the stellar mass function of L ∗ galaxies out to z ∼ 1; (b) detecting intermediate-redshift quasars at 2 ≲ z ≲ 3.5;(c) measuring the stellar mass function and baryon census of clusters of galaxies, and (d) performing cross-correlation experiments of cosmic microwave background lensing in the optical/near-infrared that link stellar mass to large-scale dark matter structure. Here we define and describe the survey, highlight some early science results, and present the first public data release, which includes an SDSS-matched catalog as well as the calibrated pixel data themselves.